2013
DOI: 10.5406/amerjpsyc.126.3.0301
|View full text |Cite
|
Sign up to set email alerts
|

The Gestural Misinformation Effect: Skewing Eyewitness Testimony Through Gesture

Abstract: The susceptibility of eyewitnesses to verbal suggestion has been well documented, although little attention has been paid to the role of nonverbal communication in misinformation. Three experiments are reported; in each, participants watched footage of a crime scene before being questioned about what they had observed. In Experiments 1 and 2, an on-screen interviewer accompanied identically worded questions with gestures that either conveyed accurate information about the scene or conveyed false, misleading in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
(66 reference statements)
6
31
0
1
Order By: Relevance
“…The use of verbal feedback in interviews is easy to identify through the use of audio recordings though, in the absence of video recording, any nonverbal feedback by comparison is likely to go undetected. Recent research highlighting the susceptibility of witnesses to misleading hand gestures (Broaders & Goldin-Meadow, 2010;Gurney et al, in press) makes a convincing case for video monitoring in interviews. Our findings that non-verbal feedback can also 248 D. J. Gurney et al…”
Section: Discussionmentioning
confidence: 99%
“…The use of verbal feedback in interviews is easy to identify through the use of audio recordings though, in the absence of video recording, any nonverbal feedback by comparison is likely to go undetected. Recent research highlighting the susceptibility of witnesses to misleading hand gestures (Broaders & Goldin-Meadow, 2010;Gurney et al, in press) makes a convincing case for video monitoring in interviews. Our findings that non-verbal feedback can also 248 D. J. Gurney et al…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this it is also important that the interviewer does not appear to assume that someone is guilty "So far as possible, the interview should be conducted in a 'neutral' atmosphere, with the interviewer taking care not to assume, or appear to assume, the guilt of an individual whose alleged conduct may be the subject of the interview" [16]. More recent research also indicated that gestures can play a significant role in leading a witness [17]. Small gestures such as head nods can affect what someone will say in an interview [17].…”
Section: Introductionmentioning
confidence: 99%
“…More recent research also indicated that gestures can play a significant role in leading a witness [17]. Small gestures such as head nods can affect what someone will say in an interview [17]. Using a robot to interview a child could eliminate any of the subtle unintentional signs in body language that a human interviewer may give away, while the body language of the robot can be fully and precisely controlled by the interviewer.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of eyewitness memory research identifies speech as the source of influence (Harris, 1973;Loftus & Palmer, 1974;Loftus & Zanni, 1975) although, increasingly, studies have found that misinformation can also occur outside speech; for example, through doctored images and photographs (Frenda, Knowles, Saletan, & Loftus, 2013;Wade, Garry, Read, & Lindsay, 2002). In addition, recent research has revealed that misinformation can be communicated nonverbally through hand gestures and that these gestures have been found to exert an influence on both adults (Gurney, Pine, & Wiseman, 2013) and children (Broaders & Goldin-Meadow, 2010). Although the effects of verbal misinformation are well stated, gestural misinformation is a relatively new concept in eyewitness research and the extent to which it compares with verbal misinformation as a form of influence is unclear.…”
mentioning
confidence: 99%
“…In the studies by Gurney, Pine, and Wiseman (2013) and Broaders and Goldin-Meadow (2010), participants were found to incorporate suggestions made through gesture into their original memory of an event. For instance, in the study by Gurney, Pine, and Wiseman, participants who were asked "do you remember any distinguishing features?"…”
mentioning
confidence: 99%